2019
DOI: 10.1016/j.jsps.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oil and n-hexane extract of Stachys tmolea subsp. Tmolea Boiss., an endemic species of Turkey, and their mosquitocidal activity against dengue vector Aesdes aegypti

Abstract: Stachys tmolea subsp. tmolea Boiss. is endemic to Turkey and is a species of the genus Stachys L. which is one of the largest genera of the family Lamiaceae with about 300 species. The aims of this study were to examine the chemical composition of the essential oil and n-hexane extract of S. tmolea subsp. tmolea as natural sources of insecticidal activity against the dengue vector, Aedes aegypti. Analysis of the essential oil by GC-FID and gas chromatography-mass spectrometry (GC-MS) systems identified hexahyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Also, diterpenes are an important group of compounds with anti-inflammatory activities [19,20]. Phytol is an acyclic diterpene alcohol, commonly found in the composition of various oils [21][22][23], which was found among the bioactive metabolites of P. russeliana n-hexane sub-extract, associated with anti-inflammatory activity [24]. Thus, in the present study, the remarkable anti-inflammatory activity of the bioactive fraction may be influenced from the phytol content.…”
Section: Bioactivity-guided Fractionation and Chemical Characterizationmentioning
confidence: 64%
See 1 more Smart Citation
“…Also, diterpenes are an important group of compounds with anti-inflammatory activities [19,20]. Phytol is an acyclic diterpene alcohol, commonly found in the composition of various oils [21][22][23], which was found among the bioactive metabolites of P. russeliana n-hexane sub-extract, associated with anti-inflammatory activity [24]. Thus, in the present study, the remarkable anti-inflammatory activity of the bioactive fraction may be influenced from the phytol content.…”
Section: Bioactivity-guided Fractionation and Chemical Characterizationmentioning
confidence: 64%
“…The identifications of the oil components were performed by comparison to their relative retention times (RRT) with those of authentic samples or compared to their relative retention index (RRI) to series of n-alkanes. The computer matching of the separated compounds against commercial (Wiley GC/MS Library, MassFinder Software 4.0) and the in-house "Başer Library of Essential Oil Constituents" built up by genuine compounds and components from literature previous reported [3,4,21]. Folin-Ciocalteu method was used for the determination of the total phenolics content of P. russeliana MeOH extract.…”
Section: Gc-fid and Gc/ms Analysesmentioning
confidence: 99%
“…However, similar activity was also observed against the non-carcinoma cell line HaCaT, indicating that it may not possess cancer-specific antiproliferative activity, although further studies are required. Although main components of the EO have been reported as main constituents in other plant extracts with similar biological activities [ 43 , 44 , 45 ], there are no available studies on the biological activities of the individual compounds, which is a valid area of further investigation. Overall, the results of our study indicated that EO form S. raeseri subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hexahydrofarnesyl acetone represented the predominated compound in all overall carotenoid-derived compounds. Hexahydrofarnesyl acetone is a common apocarotenoid-derived compound in EOs derived from the plant kingdom such as Hildegardia barteri [34], Stachys tmolea [35], and Bassia muricata [36].…”
Section: Yields and Chemical Constituents Of P Undulata Eosmentioning
confidence: 99%